Y=(-6*3)+7

Simple and best practice solution for Y=(-6*3)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y=(-6*3)+7 equation:


Simplifying
Y = (-6 * 3) + 7

Multiply -6 * 3
Y = (-18) + 7
Y = -18 + 7

Combine like terms: -18 + 7 = -11
Y = -11

Solving
Y = -11

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Simplifying
Y = -11

See similar equations:

| 3a+3b^3= | | 3(-2x)-(-3x)+1=-2x+22 | | 3x^2+4x+2=x^2+6x | | 75m+.1m=400 | | 8(2w-6)+4(-15w)=0 | | 6.3p=52.92 | | x^2-5x+4=0 | | 8(1-4b)=-35 | | -7t+-4=80 | | 2.5x=16.75 | | 4r-2=3r+6 | | 2(3x+4)-2x=x+17 | | 3f=999 | | 3-4[2-(5y-8)]= | | 4x-3x-6=21 | | -7-3x=8+2 | | 4x+x-3x+7=2x+x | | 8(x+.5)=2x+4 | | -5(2x-9)=2(x-8) | | 4x^2-10=-6x | | 2c+4-3c=-9+c+15 | | 7C+1=50 | | x-4.5=3 | | 10.6p+15=205.8 | | 10=50x | | 8s-12=52 | | -x-3x+20=x | | 3xyz-y+4x-y= | | 45p=168 | | 2f-81=11 | | 27=x+14 | | -36-9x=-12x+3 |

Equations solver categories